Human parvovirus infection in early rheumatoid and inflammatory arthritis. Issue 10 (October 1986) - Cohen, B J; Buckley, M M; Clewley, J P; Jones, V E; Puttick, A H; Jacoby, R K
Abstract : Evidence of recent infection with human parvovirus B19 (HPV) was found in two patients with early rheumatoid arthritis (RA) and in four patients with acute inflammatory arthritis (IA). Both of the patients with RA but only one of the four patients with IA carried RA associated haplotypes. No evidence of persistent infection with HPV was found, but evidence of past infection with HPV was significantly more common in patients with RA than in controls. The results confirm the arthritogenic potential of HPV and are consistent with the hypothesis that rheumatoid arthritis may develop in a genetically predisposed patient after an arthritogenic insult such as an HPV infection.